Deep-sea pollen record of MIS 31 from IODP Site 339-U1385, SW Iberian margin - Dulce Oliveira; Maria Fernanda Sanchez Goñi; Filipa Naughton; Josué M Polanco-Martínez; Francisco J Jimenez-Espejo; Joan O Grimalt; Belén Martrat; Antje H L Voelker; Ricardo M Trigo; David A Hodell; Fatima F Abrantes; Stéphanie Desprat (PANGAEA, 2025)
Pollen-based vegetation reconstruction from IODP Site U1385, drilled on the SW Iberian margin (Expedition 339, 37°34.285' N, 10°7.562' W; 2578 m below sea level). The record covers the early Pleistocene interval between 1,100 ka (MIS 32) and 1,050 ka (early MIS 30), including the interglacial MIS 31. The dataset contains counts and percentages of all identified pollen and spore morphotypes, as well as the main ecological groups: temperate forest (including Mediterranean sclerophylls and all temperate trees and shrubs, excluding Pinus, Cedrus and Cupressaceae), Mediterranean sclerophylls, and semi-desert plants. Pollen analysis: Samples of 2.5–5 cm^3 of sediment (1 cm thick slices) were taken from Holes E and D at 0.02–0.08 m intervals, and at 0.19 m intervals for transitions between holes. Processing followed the standard protocol for marine samples: coarse sieving (150 μm mesh), sequential treatments with cold HCl (10–50 %) and cold HF (45–70 %) to remove carbonates and silicates, a final cold HCl (25 %) treatment to eliminate fluorosilicates, and micro-sieving at 10 μm. Residues were mounted unstained in glycerol to allow rotation of the pollen grains. Pollen analysis of 134 samples was carried out using a Nikon light microscope at exttimes500 and exttimes1000 (oil immersion) magnification.